1995
DOI: 10.1016/s0969-2126(01)00166-6
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis for seryl-adenylate and Ap4A synthesis by seryl-tRNA synthetase

Abstract: Superposition of these structures allows a common reaction mechanism for seryl-adenylate and Ap4A formation to be proposed. The bent conformation of the ATP and the position of the serine are consistent with nucleophilic attack of the serine carboxyl group on the alpha-phosphate by an in-line displacement mechanism leading to the release of the inorganic pyrophosphate. A second ATP molecule can bind with its gamma-phosphate group in the same position as the beta-phosphate of the original ATP. This can attack t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 40 publications
3
93
0
Order By: Relevance
“…Finally, the side chain of Asp-76 moves 0.9 Å to hydrogen bond with the adenine base 6-amino group, replacing a bound water molecule in the apo-enzyme structure. These changes are consistent with the induced-fit mechanism of ATP binding, known for class II AARSs (18,19,(22)(23)(24)(25).…”
Section: Resultssupporting
confidence: 88%
“…Finally, the side chain of Asp-76 moves 0.9 Å to hydrogen bond with the adenine base 6-amino group, replacing a bound water molecule in the apo-enzyme structure. These changes are consistent with the induced-fit mechanism of ATP binding, known for class II AARSs (18,19,(22)(23)(24)(25).…”
Section: Resultssupporting
confidence: 88%
“…In similar adenylation reactions it has been suggested that a general mechanism for substrate adenylation may involve conserved arginine or lysine residues and two or three divalent cations that stabilize the pyrophosphate leaving group and the pentavalent transition-state intermediate formed during adenylation (38,39). Although we have been unable to locate magnesium ions in the current EAS structures, such stabilizing ions have been identified in the other N-type ATP pyrophosphatases and are reported to be required for maximal AS activity (30).…”
Section: Resultsmentioning
confidence: 64%
“…The 3Ј-OH of the ribose forms a hydrogen bond with the backbone carbonyl of Thr281. The triphosphate bends over the adenosine moiety, a conformation observed in the yeast AspRS (Cavarelli et al, 1994) and SerRS from T. thermophilus (Belrhali et al, 1995) and may be unique to class II aaRS ) bridge the ␤-and ␥-phosphates , which has also been observed with other class II aaRS such as SerRS and AspRS (Schmitt et al, 1998). Two Arg residues, one contributed by the motif 2 loop and the other by the motif 3 helix, interact with the ␥-phosphate.…”
Section: Crystal Structure Of Histidyl-trna Synthetasementioning
confidence: 76%